2016
DOI: 10.3390/scipharm84030497
|View full text |Cite
|
Sign up to set email alerts
|

The Study of Structure—Analgesic Activity Relationships in a Series of 4-Hydroxy-2,2-dioxo-1H-2λ6,1-benzothiazine-3-carboxylic Acid Toluidides and Xylidides

Abstract: In continuing the search for new analgesics among derivatives of 2,1-benzothiazines, a series of corresponding toluidides and xylidides of 4-hydroxy-2,2-dioxo-1H-2λ6,1-benzothiazine-3-carboxylic acid has been synthesized by the reaction of ethyl 4-hydroxy-2,2-dioxo-1H-2λ6,1-benzothiazine-3-carboxylate with equimolar amounts of mono- and dimethyl-substituted anilides in boiling dry xylene. Their structure has been confirmed by the data of elemental analysis, nuclear magnetic resonance (NMR) spectroscopy (1Н and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 21 publications
0
6
0
Order By: Relevance
“…1 ) was identified as a hit, and exhibited anti-SARS-CoV-2 activity (IC 50 = 15.3 μM). Cyclic sulfonamide derivatives are known to have various pharmacological activities such as analgesic 9 , anti-inflammatory 10 , herbicidal 11 , and antidiabetic 12 effects. Here, the present study reported the synthesis and biological effects of cyclic sulfonamide derivatives.…”
mentioning
confidence: 99%
“…1 ) was identified as a hit, and exhibited anti-SARS-CoV-2 activity (IC 50 = 15.3 μM). Cyclic sulfonamide derivatives are known to have various pharmacological activities such as analgesic 9 , anti-inflammatory 10 , herbicidal 11 , and antidiabetic 12 effects. Here, the present study reported the synthesis and biological effects of cyclic sulfonamide derivatives.…”
mentioning
confidence: 99%
“…For hetarylamides [ 15 , 16 , 19 , 20 ], as well as alkyl- [ 22 , 25 ], hydroxy- and alkoxy-substituted [ 24 ] anilides of 1-R-4-hydroxy-2,2-dioxo-1 H -2λ 6 ,1-benzothiazine-3-carboxylic acids, two directions of the primary fragmentation of molecular ions are characteristic: breaking of the heterocycle–3-carbamide fragment bond (pathway А) or destruction of the acyclic carbamide bond (pathway В). It is interesting that in the case of anilide 2a and its halogenated analogs 2b – l , this behavior ( Scheme 2 ) is recorded only in bromo-substituted derivatives 2j – l .…”
Section: Resultsmentioning
confidence: 99%
“…Secondly, halogen-substituted benzene cores have a positive effect on the analgesic properties of compounds of different chemical classes as evidenced by their presence in the structure of many drugs of this pharmacological group ( Figure 2 ) [ 18 ]. Finally, the high analgesic activity is characteristic for 4-hydroxy-2,2-dioxo-1 H -2λ 6 ,1-benzothiazine-3-carboxamides with different substituents in the terminal amide fragment, including hetaryl [ 15 , 16 , 19 , 20 ], aryl alkyl amide [ 21 ], and anilide [ 22 , 23 , 24 , 25 ] ones.…”
Section: Introductionmentioning
confidence: 99%
“…A detailed study of the crystals obtained from different solvents reveals two pseudoenantiomeric forms with significantly different analgesic effects. Taking this into account, we performed a thorough study of N-(2,6-dimethylphenyl)-4-hydroxy-2,2-dioxo-1H-2 6 ,1-benzothiazine-3-carboxamide (Scheme 2), which possesses a high analgesic activity comparable with meloxicam (Ukrainets et al, 2016b), in order to check whether such a type of polymorphism is unique or typical for derivatives of benzothiazines.…”
Section: Introductionmentioning
confidence: 99%